Drawing the City with the Ears. Urban Spaces Comprehension and Design through Auditory Perception. (November 2015) - Calleri, C.; Rossi, L.; Astolfi, A.; Armando, A.; Shtrepi, L.; Bronuzzi, F.
Abstract: This work started from one questions: Do architects use their ears while drawing a public urban space? In other words, are we aware of how an urban space sounds, as we are aware of how it looks like? By means of sounds recorded at night in different urban spaces and a three-session listening test, this work investigated urban shapes recognition through the perception of reverberance and the listeners' characteristics that work as factors of influence. A translations trough drawings of the sound perceived showed that is not always possible to represent a unique way to translate a sound into graphic signs.